(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The aim of this article is to investigate the relationship between intertextuality and the affective response to literary texts in an attempt both to strengthen the link with cognition and to investigate further aspects of the phenomenon of intertextuality. Moreover, this research will introduce a new approach to the study of intertextuality.